Qian li zou dan qi [videorecording (DVD)] = Riding alone for thousands of miles - Zhang, Yimou; Takakura, Ken, 1931-2014; Terajima, Shinobu, 1972- (Sony Pictures Home Entertainment, 2007)
Takada is an aging Japanese fisherman who has been estranged from his son for many years. When the son is diagnosed with terminal cancer his daughter-in-law, Rie, summons him to the hospital. When his son refuses to see him, Rie gives him a videotape about the work his son was doing on a documentary film in a remote region of China's Yunnan province. Still troubled by the relationship, Takada decides to go to China and complete his son's work in part to develop an understanding of his son, and in part to do something for him. Once in China a series of obstacles and relationships brings him unexpectedly closer to both an understanding of himself and of his son.